Rojava: uma revolução contra o estado - Carvalho, Eliane K. (Ecopolítica, 2017)
Resenha do livro de Dilar Dirik; David Levi Strauss; Michael Taussig; Peter Lambor Wilson (eds.). To Dare Imagining: Rojava Revolution. Nova York: Autonomedia, 2016, 154 p.